ENCRYPTION METHOD USING PASCAL’S TRIANGLE BASED SUBSTITUTION AND SIERPINSKI TRIANGLE BASED PERMUTATION - T, Sivakumar; K.T, Pauvithraa; V, Durga Devi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Text messages are often created, shared and a person sends at least ten messages a day. Because of its frequent usage those messages are not been encrypted. Thus it is unable to send confidential messages via SMS service. In this paper, we develop a new encryption technique using the notions of Pascals Triangle and Sierpinski Triangle. The proposed method uses the Pascals triangle for substitution and Sierpinski triangle for permutation. The method is simple and easy to implement in real time. It is difficult for the attackers to predict the original message contained in the ciphertext. The proposed method is not much vulnerable to brute force and letter frequency attacks.